Emotional Empathy and Facial Mimicry for Static and Dynamic Facial Expressions of Fear and Disgust - Rymarczyk, Krystyna; Żurawski, Łukasz; Jankowiak-Siuda, Kamila; Szatkowska, Iwona (Frontiers in Psychology, 2016)
Facial mimicry is the tendency to imitate the emotional facial expressions of others. Increasing evidence suggests that the perception of dynamic displays leads to enhanced facial mimicry, especially for happiness and anger. However, little is known about the impact of dynamic stimuli on facial mimicry for fear and disgust. To investigate this issue, facial EMG responses were recorded in the corrugator supercilii, levator labii and lateral frontalis muscles, while participants viewed static (photos) and dynamic (videos) facial emotional expressions. Moreover, we tested whether emotional empathy modulated facial mimicry for emotional facial expressions. In accordance with our predictions, the highly empathic group responded with larger activity in the corrugator supercilii and levator labii muscles. Moreover, dynamic compared to static facial expressions of fear revealed enhanced mimicry in the high-empathic group in the frontalis and corrugator supercilii muscles. In the low-empathic group the facial reactions were not differentiated between fear and disgust for both dynamic and static facial expressions. We conclude that highly empathic subjects are more sensitive in their facial reactions to the facial expressions of fear and disgust compared to low empathetic counterparts. Our data confirms that personal characteristics, i.e. empathy traits as well as modality of the presented stimuli, modulate the strength of facial mimicry. In addition, measures of EMG activity of the levator labii and frontalis muscles may be a useful index of empathic responses of fear and disgust.